UPAYA PENINGKATAN MOTIVASI KERJA SATUAN POLISI PAMONG PRAJA KABUPATEN TEMANGGUNG (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
This study aims to increase the work motivation of personnels of the Civil Service Police Unit in Temanggung Regency. The research was carried out starting in October 2022. This type of research is descriptive qualitative. Collection of interview and observation data. Interactive Model of Analysis. The results of the study: 1) The work motivation of members of the Civil Service Police Unit in Temanggung Regency is not optimal due to budget constraints, discipline has not been carried out optimally, awareness of Satpol PP personnels in carrying out their duties is still lacking, lack of facilities and infrastructure, communication has not gone as it should. 2) Obstacles faced related to work motivation, namely: members skills in carrying out tasks are not yet good, lack of understanding of Satpol PP personnels in carrying out tasks according to SOP, division of tasks that are not in accordance with the main tasks of personnels and compensation that does not meet personnels expectations. 3) Efforts to increase work motivation: active coordination between agencies and the legislature (DPRD) to submit budgets for improving facilities and infrastructure, assistance from superiors in carrying out tasks and giving rewards to personnels who excel and regular training and improving internal coordination.
Keywords: Motivation; Personnel; Satpol PP